Analisis Kemampuan Koneksi Matematis Siswa dalam Menyelesaikan Masalah Kontekstual - Azfa Nur Aqilah; Attin Warmi; Hanifah Hanifah (Mandalika Mathematics and Educations Journal, 2026)
This study aims to analyze students’ mathematical connection skills in solving contextual problems involving flat-sided three-dimensional shapes, based on the limited existing literature regarding students’ thought processes when connecting concepts to complex problems. The research approach adopts a qualitative case study method. The research subjects consisted of 34 ninth-grade students in class IX-H at a junior high school in Jakarta, selected to describe variations in mathematical connection skills. The instrument used was a validated mathematical connection skills test. Data were analyzed in depth through the students’ responses. The results of the study indicate significant variations in connection abilities; the majority of students were able to complete general procedures but faced difficulties with contextual problems requiring the integration of multiple concepts. A disruption in the flow of thinking was observed when students were presented with contextual problem narratives involving complex thinking stages. These findings indicate the importance of strengthening abstraction skills and problem-modeling strategies in the learning process to help students connect various mathematical concepts when solving real-world problems. Penelitian ini berupaya untuk menganalisis kemampuan koneksi matematis siswa dalam menyelesaikan permasalahan kontekstual pada materi bangun ruang sisi datar, yang didasarkan pada masih terbatasnya literatur mengenai proses berpikir siswa saat menghubungkan konsep pada masalah kompleks. Pendekatan penelitian m mengadopsi metode kualitatif jenis studi kasus. Subjek penelitian terdiri dari 34 siswa kelas IX-H di salah satu SMP Jakarta yang dipilih untuk mendeskripsikan variasi kemampuan koneksi matematis. Instrumen yang digunakan berupa tes kemampuan koneksi matematis yang telah dinyatakan valid. Data dianalisis secara mendalam melalui hasil jawaban siswa. Hasil penelitian menunjukkan adanya variasi kemampuan koneksi yang signifikan, mayoritas siswa mampu menyelesaikan prosedur umum namun terkendala pada masalah kontekstual yang membutuhkan integrasi beberapa konsep. Ditemukan adanya keterputusan alur berpikir saat siswa dihadapkan pada narasi soal kontekstual dengan tahapan berpikir kompleks. Temuan ini mengindikasikan pentingnya penguatan kemampuan abstraksi dan strategi pemodelan masalah dalam proses pembelajaran untuk membantu siswa menghubungkan berbagai konsep matematika saat menyelesaikan persoalan dunia nyata.